If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8y + 3) + -1(-7y + -7) = -2 Reorder the terms: -1(3 + 8y) + -1(-7y + -7) = -2 (3 * -1 + 8y * -1) + -1(-7y + -7) = -2 (-3 + -8y) + -1(-7y + -7) = -2 Reorder the terms: -3 + -8y + -1(-7 + -7y) = -2 -3 + -8y + (-7 * -1 + -7y * -1) = -2 -3 + -8y + (7 + 7y) = -2 Reorder the terms: -3 + 7 + -8y + 7y = -2 Combine like terms: -3 + 7 = 4 4 + -8y + 7y = -2 Combine like terms: -8y + 7y = -1y 4 + -1y = -2 Solving 4 + -1y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1y = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = -2 + -4 -1y = -2 + -4 Combine like terms: -2 + -4 = -6 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6
| -3p-4=2p | | a+3-4=-1 | | -5+13x=-6x^2 | | -9v=27 | | 48-(12)= | | 3(c-22)=2(c-6) | | r^2+2r-7=0 | | 3.7=.21w | | -12h+39=-4h-7 | | 12(4x-4)=4(12x+1) | | 40+15+0.25x=45+45+0.35x | | 8(x-6)+(-3x)=5(x-6)+3 | | 2h-35=2h+15 | | -8+4=5u-3u | | 4s-6=7s+3 | | (2x+1.5).15=11.5 | | 4.2+1.7x=2.7x | | 64n^2+36=0 | | 5(u-3)-7=-9+u-1 | | n/3=12 | | -2[5-(2z+1)]-4=2(3-2) | | 27x-3x^2=60 | | 8+5n-3=8n+11-5n | | -4(2x-6)= | | .15(2x+1.5)=11.50 | | 15x=-10x^2+10 | | -10+2x= | | -4(x+5)=2(x+5) | | P^2+4p+4=0 | | 4t-8-2y+5=0 | | 2x+(4x+150)=180 | | .015(2x+1.5)=11.5 |